Low density potting adhesive

By providing a curable lightweight potting adhesive composition precursor composed of epoxy curing agent, ammonium salt curing additive, tertiary amine curing additive, epoxy resin and hollow microspheres, the problems of diversity and processing difficulty of potting insert compositions in the prior art are solved, and the applicability and efficient potting process for various applications are achieved.

CN119744276APending Publication Date: 2025-04-013M INNOVATIVE PROPERTIES CO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380055098.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-19
Filing Date
2023-07-18
Publication Date
2025-04-01

Smart Images

  • Figure BDA0005250091180000061
    Figure BDA0005250091180000061
  • Figure BDA0005250091180000081
    Figure BDA0005250091180000081
  • Figure BDA0005250091180000121
    Figure BDA0005250091180000121
Patent Text Reader

Abstract

The present disclosure provides a curable light weight potting adhesive composition precursor, the curable light weight potting adhesive composition precursor comprising: a first portion (A) comprising (i) at least one first epoxy curing agent; (ii) at least one first curing aid comprising at least one ammonium salt; (iii) at least one second curing aid selected from tertiary amines; (iv) optionally, hollow microspheres; a second portion (B) comprising (i) at least one epoxy resin; and (ii) optionally, hollow microspheres.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a curable two-part lightweight potting composition precursor and a lightweight potting composition obtained therefrom. In addition, the present disclosure also relates to a method for potting an insert. In addition, the present disclosure also relates to the use of the curable lightweight potting composition and its precursor as described herein for potting an insert, as an adhesive when bonding and joining parts, or as an edge or reinforcing filler for a honeycomb composite structure. Background Art

[0002] Transport vehicles, such as cars, ships, and especially aircraft often contain low-weight materials to reduce fuel consumption. To achieve this goal, sandwich composites with honeycomb core structures rather than solid structures are often used. In addition, in the construction of buildings, this honeycomb structure has been widely used. Usually, the honeycomb core structure is formed by metals such as aluminum or glass fiber or composites, and the cells between the honeycomb cores are gaps. The size of the gap cells in the honeycomb structure affects the mechanical properties of the structure. The larger the size, the more the weight is reduced, but the loss of mechanical strength may be greater. The gap cells in the honeycomb structure can typically range from 5mm to 10cm in at least one dimension or in all three dimensions. In order to offset the potential mechanical strength loss compared to the solid structure, the cells of the honeycomb structure are partially or completely filled with filler materials (core fillers or gap fillers).

[0003] Compositions based on epoxy resins can be used for this purpose, such as those described in WO 2010 / 117669 A1. The outer surface of the honeycomb structure is often covered with a face sheet, i.e. a resin layer, such as an epoxy resin or a phenolic resin, to further improve the overall stability of the honeycomb structure. Honeycomb structures covered with face sheets are also referred to as sandwich composites with a honeycomb core. Composite materials, in particular prepreg blanks (prepreg fibers), are increasingly used as face sheets due to their good flame retardant properties, which are particularly important for applications in the aerospace industry.

[0004] Furthermore, materials suitable for the aerospace industry and in particular for aircraft interior applications need to meet demanding property characteristics. This includes, in particular, good mechanical properties and high compressive strength, high flame retardancy and low emission of smoke and toxic fumes when burning, while also being lightweight. Composite structures comprising honeycomb structures comprising voids filled with void fillers and covered on both sides with prepregs are therefore very common in aerospace applications.

[0005] In this regard, curable lightweight compositions are used in a variety of applications such as adhesives, honeycomb void fillers, honeycomb composite edge fillers or for potting inserts. Typically, for each of these applications, there are specialized compositions and products. However, in addition to the need in the art for specialized products with improved properties, there is also a need in the art for products that can cover not only one application but a range of two or even more applications. Furthermore, there is a need for improved compositions for potting inserts that allow for easier handling and easier insertion of the potting inserts. Summary of the invention

[0006] The present disclosure provides a curable lightweight potting adhesive composition precursor, which comprises:

[0007] The first part (A), the first part (A) comprising

[0008] (i) at least one first epoxy curing agent;

[0009] (ii) at least one first curing aid comprising at least one ammonium salt;

[0010] (iii) at least one second curing aid selected from tertiary amines;

[0011] (iv) optionally hollow microspheres;

[0012] The second part (B), the second part (B) comprises

[0013] (i) at least one epoxy resin; and

[0014] (ii) Optional hollow microspheres.

[0015] The present disclosure also provides a curable lightweight potting adhesive composition obtained by curing part (A) and part (B) of the curable adhesive composition precursor as described herein.

[0016] In addition, the present disclosure relates to a method for insert potting, the method comprising the following steps:

[0017] (a) providing a curable lightweight potting adhesive composition according to the present disclosure;

[0018] (b) drilling holes in the honeycomb composite panel;

[0019] (c) placing an insert into the hole;

[0020] (d) inserting the potting composition into the void formed by the hole and the insert;

[0021] as well as

[0022] (e) curing the potting composition.

[0023] Furthermore, the present disclosure relates to the use of a curable lightweight potting adhesive composition precursor or a curable potting composition as described herein for potting inserts, as an adhesive when bonding and joining parts, as an edge or reinforcing filler for honeycomb composite structures. DETAILED DESCRIPTION

[0024] Before explaining any embodiment of the present disclosure in detail, it should be understood that the application of the present disclosure is not limited to the details of the construction and component arrangement given in the following description. The composition and method of the present disclosure can have other embodiments and can be practiced or executed in various ways. As used herein, the terms "one", "a kind of" and "said" are used interchangeably and mean one or more; and "and / or" is used to indicate that one or two described situations may occur, such as A and / or B including (A and B) and (A or B). Moreover, in this article, the range expressed by the endpoint includes all numbers contained in the range (for example, 1 to 10 including 1.4, 1.9, 2.33, 5.75, 9.98, etc.). Moreover, in this article, the expression "at least one" includes one and all numbers greater than one (for example, at least 2, at least 4, at least 6, at least 8, at least 10, at least 25, at least 50, at least 100, etc.). Moreover, it should be understood that the wording and terms used herein are for illustrative purposes and should not be regarded as restrictive. In contrast to the use of "consisting of," which is intended to be limiting, the use of "includes," "contains," "includes," or "has," and variations thereof, is intended to be non-limiting and encompass the items listed thereafter as well as additional items. Furthermore, it is understood that the term "comprising," as used herein, may also encompass the term "consisting of" in the sense of "consisting only of," but is generally used according to its commonly used meaning in the art. Thus, limiting "comprise" to "consists of" or limiting "comprising" to "consisting of" is fully encompassed by the present disclosure.

[0025] Unless otherwise indicated, the amount of a component of a composition may be indicated in % by weight (or "% wt" or "wt.-%). Unless otherwise indicated, the amounts of all components are given as 100 wt.%. If the amount of a component is indicated in mole %, the amounts of all components are given as 100 mole % unless otherwise indicated.

[0026] In the context of the present disclosure, the terms "room temperature" and "ambient temperature" are used interchangeably and refer to a temperature of 23°C (±2°C) under ambient pressure conditions of about 101 kPa.

[0027] Unless explicitly stated otherwise, all embodiments and optional features of the present disclosure can be freely combined.

[0028] A first aspect of the present disclosure is a curable lightweight potting adhesive composition precursor, the curable lightweight potting adhesive composition precursor comprising:

[0029] The first part (A), the first part (A) comprising

[0030] (i) at least one first epoxy curing agent;

[0031] (ii) at least one first curing aid comprising at least one ammonium salt;

[0032] (iii) at least one second curing aid selected from tertiary amines;

[0033] (iv) optionally hollow microspheres;

[0034] The second part (B), the second part (B) comprises

[0035] (i) at least one epoxy resin; and

[0036] (ii) (ii) Optional hollow microspheres.

[0037] A curable lightweight potting adhesive composition precursor (such as a curable lightweight potting adhesive composition precursor according to the present disclosure) is also referred to as a 2-component composition or a 2k composition. It should be understood that the first part (A) of the curable adhesive composition precursor is physically separated from the second part (B). According to the needs of the user, the first part (A) and the second part (B) are combined and thus mixed before the intended use to obtain a curable lightweight potting adhesive composition. The present disclosure also covers a curable lightweight potting adhesive composition obtained from a curable lightweight potting adhesive composition precursor and a cured composition obtained by curing the curable adhesive composition. The use of these 2k compositions provides several advantages, such as a longer shelf life; the possibility of forming a curable composition according to the needs of the user; and an easily curable composition, which itself provides the user with further processing advantages, particularly in the technical field of assembling structures from honeycomb composite materials (including gap fillers, edge fillers, adhesive bonding and potting inserts).

[0038] The curable lightweight potting adhesive composition precursor according to the present disclosure may exhibit at least one or even a combination of desirable properties, such as good handling properties (such as having low or even no viscosity problems), fast curing time of the curable adhesive composition obtained therefrom, good mechanical strength of the cured composition while being lightweight and / or having a low cured density, and improved properties, in particular for potting inserts. This combination of improved properties makes the composition according to the present disclosure highly suitable for use in aerospace, marine and commercial industries.

[0039] According to the curable potting composition precursor of the present disclosure is a lightweight composition, while also showing desired bonding and compressive strength. This makes the composition as described herein very suitable for many applications in aerospace, shipping and commercial transportation industries, particularly in combination with honeycomb composite materials. In this regard, preferably, the curable potting composition obtained by combining the part (A) and part (B) of the curable lightweight potting adhesive composition precursor according to the present disclosure shows a cured density less than 1g / cc, preferably less than 0.9g / cc, more preferably less than 0.8g / cc and more preferably less than 0.7g / cc according to DIN 53479A. This has the effect of providing improved adhesive, gap filler, edge filler and potting insert material for all applications where lightweight is important, which is especially true for the aerospace industry.

[0040] Epoxy curing agents suitable for use in the present disclosure are compounds capable of crosslinking (curing) epoxy resins. Suitable curing agents according to the present disclosure are preferably amine-based and can be selected from primary amines or secondary amines. In this regard, it is preferred that at least one first epoxy curing agent is at least one amine-based epoxy curing agent, preferably selected from diamines, polyamide-amines, phenalkamides, phenalkamines, epoxy-amine adducts, and any combination and mixture thereof. It is also preferred that the at least one first epoxy curing agent is selected from organic diamines, preferably selected from linear or branched alkyl diamines, optionally substituted aromatic diamines, optionally substituted cyclic diamines, and any combination and mixture thereof.

[0041] Preferably, the at least one first epoxy curing agent is contained in part (A) in an amount ranging from 5 wt % to 45 wt %, preferably from 10 wt % to 40 wt % and more preferably from 15 wt % to 35 wt %, based on the total weight of part (A).

[0042] The epoxy curing agent system present in part (A) preferably comprises two epoxy curing agents, a first epoxy curing agent and a second epoxy curing agent different from (i.e. chemically different from) the first epoxy curing agent. Therefore, it is preferred that part (A) further comprises at least one second epoxy curing agent different from the at least one first epoxy curing agent, preferably selected from preferably selected from diamines, polyamide-amines, polyetheramines, benzaneamides, benzaneamines, epoxy-amine adducts and any combinations and mixtures thereof, and more preferably selected from polyetheramines and polyamide-amines, even more preferably selected from polyetheramines.

[0043] Preferably, the at least one second epoxy curing agent is included in part (A) in an amount ranging from 10 wt % to 60 wt %, preferably from 15 wt % to 55 wt % and more preferably from 20 wt % to 50 wt %, based on the total weight of part (A).

[0044] Without wishing to be bound by theory, it is believed that the diamine provides fast cure characteristics to the curable adhesive due to its inherent high reactivity while further providing excellent chemical resistance after curing with the epoxy resin.

[0045] In specific aspects, the diamines useful herein may comprise the following general structure:

[0046]

[0047] in

[0048] Residue R 1 , R 2 and R 4 independently of one another may represent hydrogen or a hydrocarbon (such as an alkyl) or an alkoxy or polyoxyalkyl residue containing about 1 to 15 carbon atoms;

[0049] R 3 represents a polyether alkyl residue preferably containing about 1 to 15 carbon atoms;

[0050] n represents an integer of 1 to 10.

[0051] Select residue R 1 , R 2 and R 4 , so that the amine contains two primary amine groups.

[0052] In a specific aspect, the diamine is a polyetheramine having two primary amine moieties.The polyetheramine may have 1 to 12, or even 1 to 6, chain ether (oxygen) atoms.

[0053] In a preferred aspect, the first epoxy curing agent comprises at least one polyetheramine derived from polypropylene oxide or polyethylene oxide. Exemplary polyetheramines suitable for use herein are commercially available from Huntsman Chemicals under the trade name JEFFAMINE or commercially available from, for example, BASF, Ludwigshafen Germany under the trade name TTD (4,7,10-trioxatridecane-1,13-diamine).

[0054] Similarly, the diamine used herein is preferably a polymeric diamine, such as an amidoamine or a polyamidoamine. The polyamidoamine may be a branched or unbranched aromatic polyamidoamine or a branched or unbranched aliphatic polyamidoamine. Preferably, the polyamidoamine is an aliphatic polyamidoamine. The polyamidoamine that can be advantageously used in the context of the present disclosure is obtained as described in

[0010] to

[0029] of EP249527A1, the disclosure of which is incorporated herein by reference.

[0055] The at least one diamine may be at least one of the above-mentioned diamines, or may also include a mixture of at least two of those diamines.

[0056] Part (A) also comprises at least one curing aid comprising at least one ammonium salt. This has the following effect: the viscosity of the adhesive composition is maintained within the desired range, while the curing acceleration properties such as the ability to cure the adhesive composition as described herein under ambient conditions are not affected. This is particularly true when at least one second curing aid further described herein is used in combination with the at least one curing aid. The at least one ammonium salt of the at least one first curing aid may comprise an inorganic or organic ammonium salt. In this regard, the at least one ammonium salt of the at least one first curing aid may comprise at least one organic or inorganic anion. Preferably, the at least one ammonium salt of the at least one first curing aid is an ammonium salt according to formula 1

[0057] NR 1 R 2 R 3 R 4 X(Formula 1)

[0058] in

[0059] R 1 , R 2 , R 3 and R 4Each of X can be the same or different and is independently selected from H, linear or branched alkyl or alkoxy, preferably selected from H and linear or branched alkyl; X is selected from chloride, bromide, nitrate, sulfate, triflate, preferably selected from nitrate and triflate, more preferably nitrate. Particularly preferred is ammonium nitrate due to its advantageous properties and commercial availability.

[0060] It is also preferred that the at least one first curing aid also includes at least one metal salt. In this regard, it is preferred that the at least one metal salt includes at least one anion selected from chloride, bromide, nitrate, sulfate, thiosulfate, triflate, phosphate and any combination and mixture thereof, preferably selected from nitrate and triflate, and more preferably nitrate. The at least one metal salt preferably includes a metal cation selected from magnesium, calcium, strontium, preferably selected from magnesium and calcium, more preferably calcium. Calcium nitrate is particularly preferred, which generally produces good results in accelerating the curing reaction with epoxy compounds, even under ambient conditions, and also produces good curing speed. In a particularly preferred example of a curable adhesive composition precursor according to the present disclosure, the at least one first curing aid includes calcium nitrate and ammonium nitrate. This combination ensures excellent curing speed and good processability, such as the desired viscosity of the curable adhesive composition described herein.

[0061] It is further preferred that part (A) further comprises at least one second curing aid different from the at least one first curing aid. Preferably, the at least one second curing aid different from the at least one first curing aid is selected from the group consisting of: imidazole, imidazole salt, imidazoline or aromatic tertiary amine. Together with the at least one first curing aid as described herein, a synergistic beneficial effect on curing speed and application properties is produced. Preferably, the at least one second curing aid different from the at least one first curing aid is selected from aromatic tertiary amines, including those having the structure of formula (2):

[0062]

[0063] in

[0064] R 1 is H or alkyl, such as for example methyl or ethyl, preferably methyl;

[0065] R 2 It is CHNR 5 R 6 ;

[0066] R 3 and R 4 may be present or absent independently of each other, and when present, R 3 and R 4It is CHNR 5 R 6 ;

[0067] R 5 and R 6 Each is independently alkyl, preferably CH3 or CH2CH3.

[0068] The at least one first curing aid is preferably contained in part (A) in an amount ranging from 0.01 wt % to 10 wt %, preferably from 0.05 wt % to 7 wt %, more preferably from 0.1 wt % to 5 wt %, based on the total weight of part (A). Similarly, the at least one second curing aid is contained in part (A) in an amount ranging from 0.1 wt % to 15 wt %, preferably from 0.5 wt % to 12 wt %, more preferably from 1 wt % to 10 wt %, based on the total weight of part (A).

[0069] Part (A) and / or part (B) of the curable composition precursor as described herein further comprises a filler material capable of reducing the density of the composition, preferably hollow microspheres. Preferred are filler materials capable of reducing the density of the composition. As used herein, "capable of reducing the density of the composition" means that the filler has a lower density than a composition without filler. Fillers capable of reducing the density of the precursor include low-density inorganic fillers (i.e., a density between 0.1 and 0.5 g / cm 3 Fillers between 0.01 and 0.30 g / cm 3 The present invention relates to a filler between 100 and 200 μm, but a low-density inorganic filler is more preferred than an organic filler because the latter tends to adversely affect the compressive strength. A combination of organic fillers and inorganic fillers can be used, but an inorganic low-density filler is preferably used in an amount greater than that of the organic filler.

[0070] The low density inorganic filler is preferably selected from inorganic particles, inorganic microspheres and in particular hollow inorganic microspheres. The microspheres may be selected from a variety of materials including, for example, glass, silica, ceramic (including sol-gel derived) or zirconia.

[0071] The fillers are preferably selected so that they give the cured composition a favorable density without sacrificing its compressive strength. The hollow inorganic microspheres may exhibit a density of less than 0.5 g / cm 3 , more preferably between 0.12 g / cm 3 and 0.42g / cm 3 The filler may have an average particle size of typically less than 500 μm, or between 10 μm and 100 μm.

[0072] Preferred hollow inorganic microspheres include glass microspheres, which are commercially available, for example, from 3M Company under the trade designation Glassbubbles D32 or Scotchlite D32 / 4500.

[0073] In this regard, it is preferred that part (A) comprises hollow microspheres, preferably selected from hollow glass microspheres and hollow ceramic microspheres, more preferably selected from glass bubbles. Preferably, part (A) comprises hollow microspheres in an amount ranging from 1 wt % to 50 wt %, preferably from 5 wt % to 45 wt %, and more preferably from 10 wt % to 40 wt %, based on the total weight of part (A).

[0074] With regard to obtaining a lightweight composition, it is preferred that part (B) comprises hollow microspheres, preferably selected from hollow glass microspheres and hollow ceramic microspheres, more preferably selected from glass bubbles. In this regard, it is preferred that part (B) comprises hollow microspheres in an amount ranging from 1 wt % to 50 wt %, preferably from 5 wt % to 45 wt %, and more preferably from 10 wt % to 40 wt %, based on the total weight of part (B).

[0075] According to the part (A) of the curable adhesive composition precursor of the present disclosure and optionally part (B) may also include at least one inorganic filler material. Preferably, part (A) and / or part (B) also include at least one filler, which is selected from graphite powder, graphite flakes, carbon black, pyrogenic silica, fused silica, calcium oxide, calcium carbonate, magnesium oxide, magnesium carbonate, glass beads and any mixture and combination thereof, preferably selected from graphite flakes, carbon black, fused silica, pyrogenic silica, calcium carbonate, glass beads and any mixture and combination thereof. Part (A) may include at least one inorganic filler material, and its amount is based on the total weight of the part (A) of the composition described herein in the range of 2 wt % to 35 wt %, preferably 5 wt % to 30 wt % and more preferably 8 wt % to 25 wt %. Similarly, part (B) may include at least one inorganic filler material, and its amount is based on the total weight of the part (B) of the composition described herein in the range of 2 wt % to 35 wt %, preferably 5 wt % to 30 wt % and more preferably 8 wt % to 25 wt %. Inorganic filler materials may have at least one beneficial effect, such as reducing the density of the composition, improving the fluidity and / or processability of the composition. Inorganic filler materials are preferred over organic filler materials because they do not impair the compressive strength of the composition. Generally speaking, any inorganic filler material known in the art may be used, i.e., silica fillers, glass, ceramics, etc.

[0076] Preferably, the at least one filler material comprises at least one silica compound. The silica compound may have the effect of making the composition as described herein have improved fluidity, improved processability and increase without sacrificing the mechanical strength or water resistance of the cured adhesive obtained therefrom, etc. In this regard, it is preferred that the at least one silica compound is selected from fused silica, pyrogenic silica, perlite and any combination and mixture thereof. The silica compound as described herein may preferably be used in the form of silica particles. Preferably, the silica particles include pyrogenic silica, preferably hydrophobic pyrogenic silica, fused silica, amorphous silica particles, hollow silica particles, silica gel, calcium silicate and any combination thereof. Exemplary commercial fillers include SHIELDEX AC5 (a synthetic amorphous silica, calcium hydroxide mixture available from WR Grace, Columbia, MD, USA); CAB-O-SIL TS 720 (a hydrophobic fumed silica treated with a polydimethylsiloxane polymer available from Cabot GmbH (Hanau, Germany); AEROSIL VP-R-2935 (a hydrophobic fumed silica available from Degussa (Düsseldorf, Germany); =Glass beads type IV (250-300 microns): amorphous silica (available from 3M Deutschland GmbH, Neuss, Germany); MINSIL SF 20 (available from Minco Inc., 510 Midway, Tennessee, USA); amorphous fused silica; and APYRAL 24ESF (epoxysilane functionalized (2 wt%) aluminum trihydrate available from Nabaltec GmbH, Schwandorf, Germany). Fused silica is available, for example, from Minco Inc., Midway, USA, under the trade name MINSIL.

[0077] Furthermore, part (A) and / or part (B) preferably comprises graphite flakes, preferably expandable graphite flakes. This can have an advantageous flame retardant effect. Preferably, part (A) comprises graphite flakes (preferably expandable graphite flakes) in an amount ranging from 0.1 wt % to 10 wt %, preferably from 0.5 wt % to 8 wt % and more preferably from 1 wt % to 6 wt %, based on the total weight of part (A). Similarly, part (B) comprises graphite flakes (preferably expandable graphite flakes) in an amount ranging from 0.1 wt % to 10 wt %, preferably from 0.5 wt % to 8 wt % and more preferably from 1 wt % to 6 wt %, based on the total weight of part (B).

[0078] In many applications, particularly in aerospace applications, it is advantageous or even required that any adhesive or filler exhibits flame retardant and / or smoke suppression properties. Therefore, it is preferred that part (A) and / or part (B) also include at least one flame retardant. The at least one flame retardant is preferably selected from compounds containing red phosphorus (preferably red phosphorus powder), organophosphorus compounds, polyphosphates (such as ammonium polyphosphate) (preferably encapsulated), organic halogen compounds, metal hydroxides (preferably aluminum hydroxide and magnesium hydroxide), calcium carbonate magnesite, hydromagnesite, borates and any combination and mixture thereof, preferably selected from compounds containing red phosphorus, organophosphorus compounds, polyphosphates (such as ammonium polyphosphate) (preferably encapsulated) and metal hydroxides (preferably metal hydroxides) and any combination and mixture thereof. Based on the gross weight of part (A), the at least one flame retardant is preferably included in part (A) in an amount in the range of 0.1 wt % to 25 wt %, preferably 0.5 wt % to 20 wt %, more preferably 1 wt % to 15 wt %. Similarly, it is preferred that the at least one flame retardant is contained in part (B) in an amount ranging from 0.1 wt.-% to 20 wt.-%, preferably from 0.5 wt.-% to 15 wt.-%, more preferably from 1 wt.-% to 10 wt.-%, based on the total weight of part (B). The presence of at least one flame retardant in the composition as described herein, especially in the amount as described herein, results in a composition having good or even excellent flame retardant properties as desired or required for a composition destined for aerospace applications.

[0079] The second part (B) of the curable adhesive composition precursor according to the present disclosure comprises at least one first epoxy resin and optionally at least one second epoxy resin. In light of the present detailed description, one skilled in the art will readily identify suitable epoxy resins for use herein.

[0080] There is no particular limitation on the epoxy resins used herein. Epoxy resins are polymers having one or more epoxy functional groups. Typically, but not exclusively, the polymer comprises repeating units derived from monomers having epoxy functional groups, but epoxy resins may also include, for example, silicone-based polymers containing epoxy groups, or organic polymer particles coated with epoxy groups or modified therefrom, or particles coated with epoxy-containing polymers or dispersed therein or modified therefrom. The epoxy functional groups allow the resin to undergo a crosslinking reaction. The epoxy resin may have an average epoxy functionality of at least 1, greater than 1, or at least 2.

[0081] Any epoxy resin generally known to those skilled in the art can be used in the context of the present disclosure. The epoxy resin can be aromatic, aliphatic, alicyclic or a mixture thereof. In typical aspects, the epoxy resin used herein is aromatic. Preferably, the epoxy resin contains a glycidyl or polyglycidyl ether type moiety. Such moieties can be obtained, for example, by the reaction of a hydroxyl functional group (such as but not limited to a dihydric or polyhydric phenol or a fatty alcohol including a polyol) with an epichlorohydrin functional group. As described herein, a dihydric phenol is a phenol containing at least two hydroxyl groups (also referred to as "aromatic" hydroxyl groups) bonded to an aromatic ring of the phenol or, in the case of a polyphenol, at least two hydroxyl groups bonded to an aromatic ring. This means that the hydroxyl groups can be bonded to the same ring of the polyphenol or to different rings of the polyphenol. Therefore, the term "dihydric phenol" is not limited to phenols or polyphenols containing two "aromatic" hydroxyl groups, but also encompasses polyphenols, i.e., compounds having more than two "aromatic" hydroxyl groups.

[0082] Examples of useful dihydric phenols include resorcinol, catechol, hydroquinone, and polyphenols including p,p'-dihydroxybibenzyl, p,p'-dihydroxyphenyl sulfone, p,p'-dihydroxybenzophenone, 2,2'-dihydroxyphenyl sulfone, p,p'-dihydroxybenzophenone, 2,2-dihydroxy-1,1-dinaphthylmethane, and the 2,2', 2,3', 2,4', 3,3', 3,4', and 4,4' isomers of dihydroxydiphenylmethane, dihydroxydiphenyldimethylmethane, dihydroxydiphenylethylmethylmethane, dihydroxydiphenylmethylpropylmethane, dihydroxydiphenylethylphenylmethane, dihydroxydiphenylpropenylphenylmethane, dihydroxydiphenylbutylphenylmethane, dihydroxydiphenyltolylethane, dihydroxydiphenyltolylmethylmethane, dihydroxydiphenyldicyclohexylmethane, and dihydroxydiphenylcyclohexane.

[0083] Preferred epoxy resins include epoxy resins containing or consisting of glycidyl ethers or polyglycidyl ethers of dihydric or polyhydric phenols, such as, for example, but not limited to, bisphenol A, bisphenol F, and combinations thereof. They contain one or more repeating units derived from bisphenol A and / or F. Such ethers or such repeating units can be obtained, for example, by polymerization of glycidyl ethers of bisphenol A and / or F with epichlorohydrin. Epoxy resins of the diglycidyl ether type of bisphenol A can be represented by the following formula, wherein n represents a repeating unit (in the case of n=0, the following formula represents the diglycidyl ether of bisphenol A):

[0084]

[0085] Typically, epoxy resins are blends of several resins. Therefore, n in the above formula may represent an average value of the blend and may not be an integer, but may include values ​​such as, but not limited to, 0.1 to 2.5.

[0086] Typically, the epoxy resin is a liquid. The epoxy resin may include a solid epoxy resin used in dissolved form or dispersed in, for example, another liquid resin. Preferably, the epoxy resin is a liquid at ambient conditions (23° C., 1 bar). The epoxy resin may contain halogens, preferably bromine atoms, to make them non-flammable.

[0087] Examples of suitable and commercially available epoxy resins include diglycidyl ethers of bisphenol A (available under the trade names EPON 828, EPON 830, EPON 1001, or EPIKOTE 828 from Hexion Specialty Chemicals GmbH, Rosbach, Germany, or under the trade names DER-331 or DER-332 from Dow Chemical Co,); diglycidyl ethers of bisphenol F (e.g., EPICLON 830 from Dainippon Ink and Chemicals, Inc. or DER-354 from Dow Chemical Co, Schwalbach / Ts., Germany); diglycidyl ethers of blends of bisphenol A and bisphenol F (e.g., DER-354 from Momentive Specialty Chemicals, Columbus, USA); Other bisphenol-based epoxy resins are commercially available under the trade name EPILOX (Leuna Epilox GmbH, Leuna, Germany); flame-retardant epoxy resins are commercially available under the trade name DER 580 (a brominated bisphenol-based epoxy resin from Dow Chemical Co.). Cycloaliphatic epoxy resins are commercially available under the trade name EPINOX (Hexion Specialty Chemicals GmbH).

[0088] Preferably, part (B) of the composition as described herein comprises at least one first epoxy resin in an amount ranging from 30 wt.% to 80 wt.%, preferably from 35 wt.% to 75 wt.%, more preferably from 40 wt.% to 70 wt.%, based on the total weight of part (B).

[0089] It is further preferred that part (A) and / or part (B) (preferably part (B)) of the curable lightweight encapsulation precursor according to the present disclosure contain at least one epoxy reactive diluent and / or at least one wetting agent. Preferably, the at least one epoxy reactive diluent is an epoxy-based reactive diluent. Such reactive diluents are epoxy-containing molecules. There are no particular restrictions on the epoxy reactive diluents used herein. Any epoxy reactive diluent commonly known in the art can be used in the context of the present disclosure.

[0090] Without wishing to be bound by theory, it is believed that epoxy-based reactive diluents particularly advantageously affect the flow characteristics of the curable compositions as described herein.

[0091] In a particular aspect of the present disclosure, the epoxy reactive diluent used herein has a saturated or unsaturated cyclic backbone and preferably contains a glycidyl ether as a reactive terminal portion.

[0092] According to a preferred aspect, the epoxy reactive diluent used herein is preferably selected from the group consisting of diglycidyl ether of resorcinol, diglycidyl ether of cyclohexanedimethanol, diglycidyl ether of neopentyl glycol, triglycidyl ether of trimethylolpropane, and any mixture thereof.

[0093] Commercially available reactive diluents useful herein include, for example, "Reactive Diluent 107" (available from Hexion) and the "Epodil" series (available from Air Products and Chemical Inc, Allentown, PA, USA), specifically including EPODIL 746, EPODIL 747, EPODIL 748, and EPODIL 757.

[0094] Preferably, part (B) of the curable lightweight potting adhesive composition precursor according to the present disclosure contains at least one reactive diluent in an amount ranging from 0.5 wt % to 25 wt %, preferably from 1 wt % to 20 wt %, more preferably from 2 wt % to 15 wt %, based on the total weight of part (B).

[0095] The at least one wetting agent is preferably selected from silanes, preferably epoxy silanes. Including at least one wetting agent in part (A) and / or part (B) of a curable composition precursor as described herein has the effect of improving the wetting of the substrate surface treated with the composition according to the present disclosure. That is, the improved adhesion of the cured composition on the substrate can be achieved. In addition, the wetting of the improved substrate surface may be advantageous on many substrates. This may be the case for many composite materials or some metal surfaces and for surfaces with complex or uneven shapes.

[0096] In addition, it is desirable to adapt the viscosity to the needs of the corresponding application. Generally, it is desirable that after part (A) and part (B) are combined into a curable lightweight potting adhesive composition, the composition can be easily extruded and applied to the surface or applied to the gap or hollow edge of the substrate. Generally, the composition used for these applications is applied manually, so the force that can be used to extrude the composition from a handheld barrel device is naturally limited. Therefore, it is preferred that the curable composition according to the present disclosure shows an extrusion rate of at least 30g / min, preferably at least 40g / min and more preferably at least 50g / min. The extrusion rate can be measured as described in the experimental part of the present disclosure. In order to further adjust the viscosity of the curable composition as described herein, part (B) of the curable composition precursor may also include at least one viscosity modifier. Preferably, the at least one viscosity modifier is selected from partially or completely hydrogenated epoxy resins, phosphoric acid polyesters, silanes, more preferably selected from phosphoric acid polyesters, and any combination and mixture thereof. It is further preferred that part (B) comprises at least one viscosity modifier in an amount ranging from 0.1 to 15 wt %, preferably from 0.2 to 10 wt %, more preferably from 0.5 to 5 wt %, based on the total weight of part (B).

[0097] The curable lightweight potting adhesive composition precursor as described herein comprises part (A) and part (B) physically separated from each other, usually in a set form comprising a barrel and a mixing nozzle for part (A) and part (B). In the mixing nozzle, part (A) and part (B) are combined and mixed in situ into a curable lightweight potting adhesive composition with a certain ratio of part (A) to part (B). Preferably, the volume ratio of part (A) to part (B) is in the range of 5:1 to 1:12, preferably 3:1 to 1:10 and more preferably 1:1 to 1:5, and even more preferably about 1:2.

[0098] The present disclosure also provides a curable lightweight potting adhesive composition, which is obtained by combining part (A) and part (B) of a curable lightweight potting adhesive composition precursor. For many applications combined with lightweight manufacturing processes, especially including the use of honeycomb composite panels, the curable potting composition as described herein is showing excellent properties. In particular, it is preferred that the curable composition according to the present disclosure exhibits a density of less than 1g / cc, preferably less than 0.9g / cc, more preferably less than 0.8g / cc and more preferably less than 0.7g / cc according to ASTM D1622 after curing, and / or a compressive strength of at least 40MPa, preferably at least 41MPa and more preferably at least 42MPa at 23°C according to ASTMD695, and / or a lap shear strength of at least 12MPa, preferably at least 13MPa and more preferably at least 14MPa according to DIN EN 1465.

[0099] Hardware inserts are widely used in aircraft interior components to fasten panels to each other, and in fact anywhere else a fastener is needed. Insert potting application is a very intensive and time-consuming process. Typically, in the prior art, the process is summarized in the following steps:

[0100] 1. Drill a wide hole in the honeycomb composite panel;

[0101] 2. filling the hole with a low density void filler composition;

[0102] 3. After the void filler composition is cured, drilling a hole in the void filler that matches the size of the insert;

[0103] 4. The insert is placed into the hole obtained in step 3 and the paste adhesive is injected to bond the insert to the cured void filler.

[0104] The use of void fillers in the process according to the prior art is mainly due to its lightweight properties. The use of paste adhesives is due to their high bonding properties. Therefore, two different epoxy compositions are used in the prior art, which further complicates the process.

[0105] However, due to its combination of properties, the curable potting composition according to the present disclosure is able to act both as a void filler and as an adhesive to hold the insert in place. Thus, a much more efficient process for insert potting is achieved.

[0106] Therefore, the present disclosure further provides a method for insert potting, the method comprising the following steps:

[0107] (a) providing a curable lightweight potting adhesive composition according to the present disclosure;

[0108] (b) drilling holes in the honeycomb composite panel;

[0109] (c) placing an insert into the hole;

[0110] (d) inserting the potting composition into the void formed by the hole and the insert;

[0111] as well as

[0112] (e) curing the potting composition.

[0113] The advantage is that the process according to the present disclosure is greatly simplified, using only one potting composition, which greatly speeds up the process and saves materials, equipment, time and personnel training. The honeycomb composite board used in the present process itself is well known in the art. This is also true for the method and equipment for drilling holes and the inserts to be potted. Basically, any insert known in the art can be potted and used in the method as described herein, respectively. Preferably, the insert is a hardware insert for manufacturing aircraft. Regarding curing to a curable potting composition, it is preferred that the curing step is carried out at a temperature in the range of 15°C to 40°C, preferably 18°C ​​to 35°C and more preferably 20°C to 30°C. This has the advantage that no additional equipment is required for heating the board or composition. That is, the method as described herein can be carried out under ambient conditions.

[0114] The present disclosure also provides the use of the curable lightweight potting adhesive composition precursor or the curable potting composition as described herein for potting inserts, as an adhesive when bonding and joining parts, as an edge or reinforcing filler of a honeycomb composite structure. Preferably, the use includes the use of honeycomb composite materials in the aerospace industry, the shipbuilding industry, the automotive industry or the commercial transportation industry, preferably in the aerospace industry.

[0115] Example

[0116] The present disclosure is further described, however, it is not intended to be limited thereto. The following examples are provided to illustrate certain embodiments but are not intended to be limiting in any way. Prior to this, some test methods for characterizing materials and their properties will be described. Unless otherwise indicated, all parts and percentages are by weight.

[0117] Example

[0118] Materials used :

[0119] raw materials describe effect Epikote 232 Bisphenol A / F epoxy resin Base resin Disparlon 6500 Polyamide wax Collapse resistance Epodil 757 Cyclohexanedimethanol diglycidyl ether Reactive diluent BYK W 9010 Copolymers with acidic groups Dispersing Additives Kronos 1230 Titanium Dioxide pigment Exolit RP6500 Encapsulated red phosphorus in epoxy resin Flame retardants Exolit AP462 Microencapsulated ammonium polyphosphate Flame retardants Glass Bubble Glass Microspheres Lightweight filler Graphite Sheet Expandable graphite Flame retardants TTD Trioxatridecanediamine (TTD) Curing agent Ancamine 2422 Benzene-1,3-dimethylamine (MXDA) Curing agent Calcium nitrate hydrate Calcium nitrate tetrahydrate Curing aid Versamine EH50 Tertiary amine Curing aid Ancamine K54 Tris-(dimethylaminomethyl)phenol Curing aid Calcium ammonium nitrate hydrate Calcium ammonium nitrate hydrate Curing aid Aerosil R202 Fumed Silica filler

[0120] Test Method

[0121] Curing rate

[0122] Determine cure rate by measuring lap shear strength as described below (except described curing procedure).Apply sample with the adhesive composition mixed and make it solidify at room temperature.Then test lap shear strength after certain interval.The shear strength that relatively passes over time provides the indication of cure rate, i.e. the comparison of cure rate that different embodiments and comparative example pass over time.

[0123] Extrusion rate

[0124] The processability of the curable composition was evaluated at room temperature (23° C.) by extruding it through a standard apparatus using the following procedure. An air-driven application pistol (available from SEMCO, East Kilbride, UK) was equipped with a 150 ml disposable cartridge and a nozzle having a 4 mm orifice. The disposable cartridge was filled with the curable composition and extruded by applying an air pressure of 4 bar. The extrusion rate was determined by measuring the amount extruded in 15 seconds.

[0125] The measurement was performed immediately after the preparation of the curable composition (initial extrusion rate). Each curable composition was evaluated three times and the results were averaged.

[0126] Lap shear strength according to DIN EN 1465 (published in 2009)

[0127] According to DIN EN 1465, a Zwick Z050 tensile tester (commercially available from Zwick GmbH & Co. KG, Ulm, Germany) was used on a 100 mm x 25 mm x 0.8 mm thick steel sheet coated with 3 g / m 2 The lap shear strength was determined on an aluminum substrate coated with a dry lubricant coated with oil (PL 3802-39S, commercially available from Fuchs Petrolub AG, Germany) at a crosshead speed of 10 mm / min. To prepare the lap shear strength test assembly, the epoxy film to be tested (having a thickness of 0.4 mm) was applied to one end of a first steel strip and covered by a second steel strip, thereby forming a 10 mm lap joint. The lap joint was then clamped together using two binder clips, and the test assembly was placed in an air circulating oven with a minimum baking cycle of 20 min at 160°C and a maximum baking cycle of 45 min at 200°C. Here, the test assembly was heated and cooled using a gradient of 3°C / min. The test assembly was then conditioned for 24 hours under ambient conditions of 23+ / -2°C and 50+ / -%% relative humidity before testing. Prior to testing on a Zwick tensile tester, the test assemblies were placed in an environmental chamber (commercially available from RS Simulatoren, Oberhausen, Germany) and the lap shear strength was measured at room temperature (23°C + / - 2°C). Three samples of each example were measured at three different test temperatures, and the results were then averaged and reported in MPa.

[0128] Adhesive peel strength according to ASTM 1876 (published in 2008)

[0129] According to ASTM 1876, a Zwick Z050 tensile tester (commercially available from Zwick AG, Ulm, Germany) was used on a sheet having the following dimensions: 150 mm×25 mm×0.8 mm and coated with 3 g / m 2 Adhesive peel strength was measured on aluminum substrates coated with dry lubricant oil (PL 3802-39s, commercially available from Volkswagen Group, Germany). For all measurements, the crosshead speed was set to 100 mm / min and the adhesive peel strength was measured at 23°C + / - 2°C and 50 + / - 5% relative humidity. For test assembly preparation, masking tape (Scotch TM 2610 masking tape, commercially available from 3M Company, USA) is applied to the first steel strip. The masking tape is thus applied to visualize the bonding area. The bonding area has a size of 100mm×25mm. Then the embodiment material to be tested is applied to the marked bonding area and covered with a second steel strip with the same size as the first steel strip. Afterwards, the two steel strips are first pressed together manually, and then clamped together along the bonding line using 2 binder clips to fix the test assembly in place. The test assembly is cured in an air circulation oven with a minimum baking cycle of 160°C 20min and a maximum baking cycle of 200°C 45min. Here, the test assembly is heated and cooled using a gradient of 3°C / min. Then, the test assembly is placed under environmental conditions of 23+ / -2°C and 50+ / -5% relative humidity for 24 hours before testing. For each embodiment material, 3 adhesive peel strength test assemblies are prepared, and the test results are averaged. The test results are reported in N / 25mm.

[0130] Cured density

[0131] The density of the cured epoxy-based composition is measured according to DIN 53479A. The samples of the epoxy-based composition are prepared by pouring the corresponding precursor into a mold and curing at ambient temperature for at least 48 hours. The cured samples of the epoxy-based composition are removed from the mold and their exact dimensions are recorded. Each sample is weighed and the weight is reported in g / cm 3 Calculate and record the density for the units.

[0132] Compressive strength according to ISO 604

[0133] 200 g of the curable composition were cast into a release-coated mold having dimensions of 12.5 mm (height) x 12.5 mm (width) x 25 mm (length) and open on one major side. The curable composition was then allowed to cure at room temperature for 48 h.

[0134] All test specimens were compressed along the 25 mm axis of the test specimen at a rate of 0.5 mm / min using a Zwick Model Z050 tensile testing machine (Zwick GmbH & CO., Ulm, Germany) with heating capabilities.

[0135] The compressive strength was measured at 23°C (room temperature). Prior to testing, the test specimens were preconditioned at room temperature for at least 30 minutes.

[0136] Six samples were measured for each epoxy composition. The results were averaged and reported in MPa.

[0137] Preparation of Part (A) and Part (B)

[0138] Part (A) and Part (B) were prepared using the ingredients listed in Table 1 and Table 2 according to the procedure listed below.

[0139] Part A Example 1 Comparative Example 1 Ancamine 2422 20 25 Baxxdur EC130 40 25 Calcium Nitrate 0 5.5 Calcium nitrate / ammonium nitrate 1:1 1 0 Versamine EH50 0 10 Ancamine K54 4 0 Hydrated aluminum 0 10.5 Exolit AP462 8 0 Polyamide wax 0.5 1 Expandable graphite 2 0 Glass Bubble 20 23 Aerosil R202 4.5 0 total 100 100

[0140] Table 1 : Composition of part (A). All ratios are given in % by weight.

[0141] Part B Example 1 Comparative Example 1 Epon 232 53 32 Polyamide wax 1 1 Epodil 757 10 17 Exolit RP6500 2 2 Epoxy silane 0 3 Dispersing Additives 1 1 Expandable graphite 3 4 filler 3 4 Aluminum trihydrate 0 9 Exolit AP462 7 Glass Bubble 18 27 Aerosil R202 2 total 100 100

[0142] Table 2 : Composition of part (B). All ratios are given in % by weight.

[0143] Part A :

[0144] Part (A) is prepared by adding calcium nitrate (Comparative Example 1) or calcium nitrate or ammonium nitrate mixture) to the primary curing agent and mixing for 2 minutes in a high-speed mixer (3000 U / min). After the calcium nitrate is fully dispersed, the filler is then added and mixing continues for another 2 minutes. Afterwards, ancamine K54 (Example 1) or versamine EH10 (Comparative Example 1) is added and mixed. In the last step, part (A) is degassed under vacuum for 2 minutes while mixing. The degassed part A is then filled into one side of a 200 mL double Pac cartridge.

[0145] Part B :

[0146] The base resin was made by mixing epoxy resin and flame retardant in a high speed mixer for 1 minute. The filler was then added in steps and mixed several times until a uniform mixture was obtained. The mixture was then degassed under vacuum for 2 minutes while mixing. The degassed Part B was filled into the other side of the Dual Pac cartridge. The mixing ratio of Part (A) to Part (B) by volume was 1:2.

[0147] Evaluate :

[0148] The extrusion rate, cured density, compressive strength and lap shear strength were tested. As Comparative Example 1, a commercially available 2K epoxy structural adhesive composition was used. The results are summarized in Table 3.

[0149] parameter Test Method Comparative Example 1 Example 1 Extrusion Double packing tube 45g / min 70g / min Cured density DIN 53479A 0.60g / cc 0.66g / cc Compressive strength at 23°C ISO 604 45Mpa 44MPa Lap shear strength DIN EN 1465 11MPa 15MPa

Claims

1. A curable lightweight potting adhesive composition precursor, the curable lightweight potting adhesive composition precursor comprising: The first part (A), the first part (A) comprising (i) at least one first epoxy curing agent; (ii) at least one first curing aid comprising at least one ammonium salt; (iii) at least one second curing aid selected from tertiary amines; (iv) optionally hollow microspheres; The second part (B), the second part (B) comprises (i) at least one epoxy resin; and (ii) Optional hollow microspheres.

2. The curable lightweight potting adhesive composition precursor according to claim 1, wherein the curable potting composition obtained by combining part (A) and part (B) of the curable lightweight potting adhesive composition precursor according to claim 1 exhibits a cured density according to ASTM D1622 of less than 1 g / cc, preferably less than 0.9 g / cc, more preferably less than 0.8 g / cc and more preferably less than 0.7 g / cc.

3. The curable lightweight potting adhesive composition precursor according to claim 1 or claim 2, wherein the at least one first epoxy curing agent is at least one amine-based epoxy curing agent, preferably selected from diamines, polyamide-amines, benzaneamides, benzaneamines, epoxy-amine adducts and any combinations and mixtures thereof.

4. The curable lightweight potting adhesive composition precursor according to claim 3, wherein the at least one first epoxy curing agent is selected from organic diamines, preferably selected from linear or branched alkyl diamines, optionally substituted aromatic diamines, optionally substituted cyclic diamines, and any combination and mixture thereof. 5 . The curable lightweight potting adhesive composition precursor according to claim 1 , wherein the at least one ammonium salt of the at least one first curing aid comprises an inorganic or organic ammonium salt.

6. The curable lightweight potting adhesive composition precursor according to any one of the preceding claims, wherein the at least one ammonium salt of the at least one first curing aid comprises at least one organic or inorganic anion.

7. The curable lightweight potting adhesive composition precursor according to any one of the preceding claims, wherein the at least one ammonium salt of the at least one first curing aid is an ammonium salt according to Formula 1 NR 1 R 2 R 3 R 4 X(Formula 1) in R 1 , R 2 , R 3 and R 4 Each of can be the same or different and is independently selected from H, linear or branched alkyl or alkoxy, preferably selected from H and linear or branched alkyl; X is selected from chloride, bromide, nitrate, sulfate, triflate, preferably selected from nitrate and triflate, more preferably nitrate.

8. The curable lightweight potting adhesive composition precursor according to any one of the preceding claims, wherein the at least one first curing aid further comprises at least one metal salt.

9. The curable lightweight potting adhesive composition precursor according to claim 8, wherein the at least one metal salt comprises a metal cation selected from magnesium, calcium, strontium, preferably selected from magnesium and calcium, more preferably calcium.

10. The curable lightweight potting adhesive composition precursor according to claim 8 or claim 9, wherein the at least one first curing aid comprises calcium nitrate and ammonium nitrate.

11. The curable lightweight potting adhesive composition precursor according to any one of the preceding claims, wherein the at least one second curing aid is selected from aromatic amines, preferably from phenolic amines.

12. The curable lightweight potting adhesive composition precursor according to any one of the preceding claims, wherein part (A) and / or part (B) comprises hollow microspheres, preferably selected from hollow glass microspheres and hollow ceramic microspheres, more preferably selected from glass bubbles.

13. A curable lightweight potting composition obtained by combining part (A) and part (B) of the curable potting precursor according to any one of the preceding claims.

14. A method for potting an insert, the method comprising the following steps: (a) providing a curable lightweight potting adhesive composition according to claim 13; (b) drilling holes in the honeycomb composite panel; (c) placing an insert into the hole; (d) inserting the potting composition into the void formed by the hole and the insert; as well as (e) curing the potting composition.

15. Use of the curable lightweight potting adhesive composition precursor according to any one of claims 1 to 12 or the curable potting composition according to claim 13 for potting inserts, as an adhesive when bonding and joining parts, as an edge or reinforcing filler for honeycomb composite structures.

Citation Information

Patent Citations

  • Method and apparatus for seismic data processing by correlation

    EP0249527A2

  • Epoxy resin based core filler material developing low exothermic heat

    WO2010117669A1